Efektivitas Penerapan Prinsip Keadilan dalam Putusan Nafkah Pasca Perceraian: Studi Kasus di Pengadilan Agama Kelas IA Palu - Sulfiani, Andi; Thahir, Lukman S.; Musyahida, Sitti; Ibrahim, Ibrahim (Jurnal Ragam Pengabdian, 2026)
This study evaluates and analyzes the effectiveness of the application of the principle of justice in alimony decisions at the Class IA Religious Court of Palu. Using an empirical legal approach, this qualitative research examines how the substantive, formal, and distributive principles of justice are integrated into decisions regarding nafkah iddah, mut’ah, and child support. Data sources consist of primary data collected from interviews with judges alongside detailed analyses of court judgements, specifically No. 961/Pdt.G/2024/PA.Pal and No. 205/Pdt.G/2026/PA.Pal. The findings indicate that the application of the principle of justice has been implemented comprehensively through distributive and restorative justice perspectives by integrating mediation agreements directly into court decrees. Furthermore, judicial policies regarding the determination of alimony levels demonstrate dynamic flexibility that safeguards the economic security of vulnerable women and children.